Mathematical modeling of labial surface planes in maxillary central incisors - Dorriz H.; Afzalifar R.; Afzalifar B. (Tehran University of Medical Sciences, 2007)
Background and Aim: As central incisors have a prominent role in esthetics, appropriate preparation, considering natural tooth anatomy and proper planes have always been considered. The aim of this study was to determine the number of planes in labial surface of maxillary central incisors using image processing and mathematical analysis.Materials and Methods: This pilot study was performed on 32 intact maxillary central incisors in dental students of Tehran university of medical sciences. Photographs were taken from profile view of each tooth by a digital camera. Images were processed and number of planes was obtained using SigmaScan Pro. version 5.00 software and a customized program. Data were analyzed by t-test and regression tests with p<0.05 as the level of significance.Results: 96.9% of central incisors had three planes and 3.1% had two planes in labial surface. The angle between middle-cervical and middle-incisal planes showed statistically significant difference (p< 0.01).Conclusion: Based on the results of this study, a few percentage of maxillary central incisors had two planes and most of them had three planes in their labial surfaces. Thus, considering three planes for restoring maxillary central teeth is closer to principles of tooth preparation and esthetics.